2023
DOI: 10.2147/ijn.s434842
|View full text |Cite
|
Sign up to set email alerts
|

A Review of in vivo Toxicity of Quantum Dots in Animal Models

Xiaotan Lin,
Tingting Chen

Abstract: Tremendous research efforts have been devoted to nanoparticles for applications in optoelectronics and biomedicine. Over the past decade, quantum dots (QDs) have become one of the fastest growing areas of research in nanotechnology because of outstanding photophysical properties, including narrow and symmetrical emission spectrum, broad fluorescence excitation spectrum, the tenability of the emission wavelength with the particle size and composition, anti-photobleaching ability and stable fluorescence. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 237 publications
0
4
0
Order By: Relevance
“…The limited understanding of QDs' biological interactions calls for in-depth research into their physicochemical properties and their behavior within the body. 39 The safety concerns are heightened with cadmiumbased QDs, prompting a shift toward developing heavy-metalfree alternatives. Innovations such as chitosan-derived QDs show promise in biocompatibility and low toxicity, 40,41 indicating progress toward overcoming these hurdles.…”
Section: Research Hotspots Of Nanotechnology In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…The limited understanding of QDs' biological interactions calls for in-depth research into their physicochemical properties and their behavior within the body. 39 The safety concerns are heightened with cadmiumbased QDs, prompting a shift toward developing heavy-metalfree alternatives. Innovations such as chitosan-derived QDs show promise in biocompatibility and low toxicity, 40,41 indicating progress toward overcoming these hurdles.…”
Section: Research Hotspots Of Nanotechnology In Sepsismentioning
confidence: 99%
“…Despite these advancements, the clinical application of QDs faces significant challenges, particularly in regards to acute and long-term toxicity. The limited understanding of QDs’ biological interactions calls for in-depth research into their physicochemical properties and their behavior within the body . The safety concerns are heightened with cadmium-based QDs, prompting a shift toward developing heavy-metal-free alternatives.…”
Section: Research Hotspots Of Nanotechnology In Sepsismentioning
confidence: 99%
“…Extensive in vitro and in vivo studies have shown promising results regarding the low toxicity of GQDs. 15 In addition, the biocompatibility of GQDs can vary depending on their specific characteristics, concentration, and the targeted biological system. More systematic studies are required to fully understand the long-term effects and potential risks associated with their use.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…In this context, further exploration is still warranted to address the limitations concerning bio-persistence, organ accumulation, variability, and potential human health impacts, in order to develop safer technologies based on GQDs. 15 Besides, the photothermal conversion efficiency of GQDs is a critical factor for effective cancer therapy. Enhancing the photothermal conversion efficiency of GQDs will maximize their ability to generate localized hyperthermia and induce cancer cell death.…”
Section: Introductionmentioning
confidence: 99%